2009
DOI: 10.1586/era.09.44
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic nephrectomy for Wilms’ tumor

Abstract: The role of minimally invasive surgery for the treatment of pediatric urological tumors has been limited to biopsies and resection for small neuroblastomas and benign tumors. The purpose of this study is to present the experience of a Brazilian group pioneering laparoscopic nephrectomy for Wilms' tumor. A total of 15 children with unilateral non-metastatic Wilms' tumor were preoperatively treated with vincristine and actinomycin D, and afterwards were submitted to laparoscopic nephrectomy and lymph node sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 61 publications
1
33
1
1
Order By: Relevance
“…In adults, MIS is regularly used for the surgical treatment of renal malignancies [20]. In children, Wilms tumors (WT) are more and more often resected laparoscopically, however, only infrequent analyses have been published by now, mostly reporting on small patients' cohorts [12][13][14]21,22]. Very recently, Varlet et al published the first multi center study on 17 children undergoing laparoscopic nephrectomy for renal malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, MIS is regularly used for the surgical treatment of renal malignancies [20]. In children, Wilms tumors (WT) are more and more often resected laparoscopically, however, only infrequent analyses have been published by now, mostly reporting on small patients' cohorts [12][13][14]21,22]. Very recently, Varlet et al published the first multi center study on 17 children undergoing laparoscopic nephrectomy for renal malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…MIS also plays a certain role in pediatric surgical oncology although the exact relevance in most entities has not yet been determined [9][10][11]. The use of MIS in patients suffering from WT has been reported in singular cases [12][13][14], however, a systematic analysis has not been undertaken so far and by now there are no evidence based data available. This is of importance since the minimally invasive approach seems to be increasingly used.…”
mentioning
confidence: 99%
“…This is usually done in conjunction with preoperative chemotherapy and is likely more feasible after the tumor is reduced in size [41]. Experience with open nephrectomy after chemotherapy has shown that these tumors are less prone to tumor spillage [42].…”
Section: Surgerymentioning
confidence: 99%
“…However, most series reporting on the subject advocate for the open surgical approach [9][10][11][12][13][14]. Minimally invasive surgery has been used successfully for radical nephrectomy after neoadjuvant chemotherapy in cases of pediatric unilateral WT [15,16]. In the adult population, laparoscopic NSS has been demonstrated to be safe with benefits in terms of recovery time and postoperative complications in the treatment of early renal cancer [17].…”
Section: Discussionmentioning
confidence: 99%